Implementación de Buenas Prácticas Corporativas para la mejora de la Gestión Operativa en la Agencia 1 Banco de la Nación Trujillo año 2018. - Gálvez Salazar, Kiriam Keller (2019)
ABSTRACT This thesis is entitled "IMPLEMENTATION OF GOOD CORPORATE PRACTICES FOR THE IMPROVEMENT OF OPERATIONAL MANAGEMENT IN THE AGENCY 1 BANK OF THE NATION TRUJILLO YEAR 2018", it has posed the following problem to what extent the implementation of Good Corporate Practices in the process of attention the client will improve operational management in the 1 Trujillo Bank of the Nation Agency - Year 2018. Likewise, the general objective is to evaluate the implementation of Good Corporate Practices and its improvement in operational management. The materials that were used were made up of the officers and operative servants that work in the office of the 1 Trujillo Bank of the Nation and the applied method is INDUCTIVE- DEDUCTIVE by means of this method the reality of the Banco de la Nación is known starting from the general to the particular. As a main result, it has been determined that the implementation of the Good Corporate Practices allows to improve the Operational Management of the Agency 1 Banco de la Nación in the district of Trujillo. Conclusion of this, the present thesis has achieved as a result, assess the improvement in operational management optimizing 55% in the time used for the attention of the banking processes in the agency 1 bank of the nation Trujillo to the year 2018.